Effect of the load level in the fire resistance of composite slab with steel decking - Balsa, Carlos (2019)
consists of cold-formed profiled steel deck which acts as a permanent formwork to the concrete topping. Normally, this composite solution requires the addition of other components such as steel rebars (placed within the ribs) for positive bending and steel mesh for negative bending, preventing cracks in concrete, see Figure 1. Due to the external reinforcement provided by the steel deck, composite slabs generally require less additional reinforcement and less concrete as well, resulting in slender slabs. In addition, the reduction of the construction time, elimination or reduction of struts and the simplicity of installation, are other advantages of composite slabs in comparison to conventional flat concrete slabs. The composite action between the concrete and the steel deck is generally achieved by indentations or embossments in the steel deck.